A case study of the development of the environmental education section of the Western Cape standard six general science interim syllabus (1995) and the related learner material of the Science Education Project - Abrahams, Mogamat Faldee (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ed.) -- University of Stellenbosch, 1997.